Comparative study of immune response to local tumor destruction modalities in a murine breast cancer model - Budhu, Sadna; Kim, Kwanghee; Yip, Wesley; La Rosa, Stephen; Jebiwott, Sylvia; Cai, Liqun; Holland, Aliya; Thomas, Jasmine; Preise, Dina; Somma, Alex; Gordon, Benjamin; Scherz, Avigdor; et al. (Frontiers in Oncology, 2024)
Introduction Immunotherapy is revolutionizing the management of multiple cancer types. However, only a subset of patients responds to immunotherapy. One mechanism of resistance is the absence of immune infiltrates within the tumor. In situ vaccine with local means of tumor destruction that can induce immunogenic cell death have been shown to enhance tumor T cell infiltration and increase efficacy of immune checkpoint blockade. Methods Here, we compare three different forms of localize tumor destruction therapies: radiation therapy (RT), vascular targeted photodynamic therapy (VTP) and cryoablation (Cryo), which are known to induce immunogenic cell death, with their ability to induce local and systemic immune responses in a mouse 4T1 breast cancer model. The effects of combining RT, VTP, Cryo with anti-PD1 was also assessed. Results We observed that RT, VTP and Cryo significantly delayed tumor growth and extended overall survival. In addition, they also induced regression of non-treated distant tumors in a bilateral model suggesting a systemic immune response. Flow cytometry showed that VTP and Cryo are associated with a reduction in CD11b+ myeloid cells (granulocytes, monocytes, and macrophages) in tumor and periphery. An increase in CD8+ T cell infiltration into tumors was observed only in the RT group. VTP and Cryo were associated with an increase in CD4+ and CD8+ cells in the periphery. Conclusion These data suggest that cell death induced by VTP and Cryo elicit similar immune responses that differ from local RT.